2004
DOI: 10.1088/0305-4470/37/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Theta-function parametrization and fusion for 3D integrable Boltzmann weights

Abstract: We report progress in constructing Boltzmann weights for integrable 3dimensional lattice spin models. We show that a large class of vertex solutions to the modified tetrahedron equation can be conveniently parameterized in terms of N -th roots of theta-functions on the Jacobian of a compact algebraic curve. Fay's identity guarantees the Fermat relations and the classical equations of motion for the parameters determining the Boltzmann weights. Our parameterization allows to write a simple formula for fused Bol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The other known solutions, previously found by Hietarinta [9] and Korepanov [10], were shown to be special cases of [8]. A review of the most recent activity related to the TE can be found in the work of von Gehlen, Pakulyak and Sergeev [11].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…The other known solutions, previously found by Hietarinta [9] and Korepanov [10], were shown to be special cases of [8]. A review of the most recent activity related to the TE can be found in the work of von Gehlen, Pakulyak and Sergeev [11].…”
Section: Introductionmentioning
confidence: 70%
“…It is particularly useful for constructing integrable evolution systems on a 2 + 1-dimensional lattice and can be viewed as a three-dimensional lattice analog of the Lax-Zakharov-Shabat zero-curvature condition in two dimensions (see [44] for further details). Suppose now, that the algebra A has a "quasi-classical" limit when it degenerates into a Poisson algebra P. In this limit all the generators v i , i = a, b, c, become commutative formal variables, and the relation (11) becomes a c-number equation which very much resembles the usual quantum Yang-Baxter equation (but does not coincide with it). The quasi-classical limit of the map (7) defines a symplectic transformation of the tensor cube of the Poisson algebra P, which, of course, solves the same functional TE (9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations